REALISASI KESANTUNAN BERBAHASA ANTARA KEPALA SEKOLAH DENGAN GURU DAN STAF SMA MUHAMMADIYAH 4 ANDONG - SUGIYANTO , SUGIYANTO (2011)
In communication we often find that every speech always involves to feeling. Because sometime every individual does not realize that his or her speech can inflict other such occures among staff of SMA Muhammadiyah 4 Andong. Every individual has own characteristic in communication. As communication which is done by principal, vice principal of curriculum, vice principal of student consultant, teacher, and administration staff (TU), the speech as follow. After studyng the principal's speech toward description table, the result is that 90% of principal's speech is in the form of command, while 10% is persuading form. It can be said that the realization of modesty by the principal of SMA Muhammadiyah 4 of Andong is relatively low. Vice principal of curriculum's speech is relatively medium. It means that he uses almost all form of speech, it can be command, asking, persuading and showing. It can be calculated as follow; 40% command, 30% asking speech, 20% asking, and 20 % showing. The speeches of teacher of SMA Muhammadiyah 4 of Andong is 90% persuading, while 10% is in the form of asking. In conclusion, the realization of teacher's speech of SMA Muhammadiyah 4 of Andong is relatively high. Administration staff (TU) speech is 90% in the form of persuading, and 10% is questioning form. It can be pointed out that the realization of speech of administration staff is relatively high. The speech of vice principal of curriculum and vice principal of student consultant is realtively same. But vice principal of student consultant speech tends to command comparated to vice principal of curriculum. It can be said that the realization of modesty which is expressed by vice principal of student consultant is only 49%. In conclusion, vice principal of student consultan's communication is not modest yet. It's based on data reduction from the result of speeches which are expressed.